Fatigue among patients with cancer [Kanser hastalarinda yorgunluk] - (:unkn) unknown (My University, 2002)
Fatigue is the most common and disturbing complaint reported by patients with cancer, but little is known about the mechanisms influencing it. In this review article we investigated that fatigue related to cancer and made some recommendations to help patients with fatigue.